2017
DOI: 10.20453/rmh.v28i2.3108
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a la anticoagulación oral óptima en el adulto mayor con fibrilación auricular

Abstract: RESUMENObjetivos: Determinar la calidad del control de la anticoagulación oral y los posibles factores asociados al tiempo de rango terapéutico. Material y métodos: Estudio retrospectivo con grupo control y exploración de posibles variables, realizado en pacientes ≥65 años con fibrilación no valvular e indicación de anticoagulación del Hospital Cayetano Heredia entre el 2011-2013. Se determinó el tiempo de rango terapéutico (TRT) por el método de Rosendaal y se consideró control óptimo (TRT ≥60%) y subóptimo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…12 Previous investigations on factors associated with anticoagulation control have shown a relationship between TTR and sex, albeit with conflicting evidence. Some authors reported an association of females with poorer TTR, although others found poorer TTR in men [13][14][15] or no association of oral anticoagulation control with sex. 16,17 Sex-related aspects that may affect TTR, such as behavioural and physiological factors, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…12 Previous investigations on factors associated with anticoagulation control have shown a relationship between TTR and sex, albeit with conflicting evidence. Some authors reported an association of females with poorer TTR, although others found poorer TTR in men [13][14][15] or no association of oral anticoagulation control with sex. 16,17 Sex-related aspects that may affect TTR, such as behavioural and physiological factors, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about the use of anticoagulants in Latin America confirm this information. Gamero et al, in a study performed in Peru in 2017, found that 95% of people with oral anticoagulation received warfarin and only 5% took direct oral anticoagulants, attributing this phenomenon to a subject of costs (29).…”
Section: Discussionmentioning
confidence: 99%
“…(5) La prevalencia de la FA se multiplica con la edad, es por tanto, un problema sanitario muy relevante a nivel poblacional, esto se debe no solo a su alta prevalencia e incidencia, sino también por los elevados costos que se derivan de las complicaciones que conlleva. (3,6) El ictus isquémico es la complicación más importante, con un riesgo relativo (RR) 2-7 veces mayor que el de los pacientes sin FA. El incremento del riesgo de hemorragia, especialmente la temida hemorragia intracraneal, acompaña al tratamiento con anticoagulantes orales.…”
Section: Introductionunclassified